2023
DOI: 10.3389/fmed.2023.1270486
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric patient in the practice of emergency medical teams – observation in 2020–2022

Łukasz Czyżewski,
Łukasz Dudziński,
Janusz Wyzgał

Abstract: PurposeAnalysis of interventions of medical rescue teams for geriatric patients in a three-year period, taking into account the causes, circumstances, medical management, pharmacology.Materials and methodsThe study included a 3-year retrospective analysis of the trips of medical rescue teams in the northern part of the Lubelskie Voivodeship in the period from January 1, 2020 to December 31, 2022. The data comes from medical documentation. Interventions caused by a health risk in a patient in the 90+ age group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Any preventable transfer Health Problems of Civilization eISSN: 2354-0265, ISSN: 2353-6942 exposes the patient to transport-related complications, and contributes to excessive emergency department occupancy, and increased costs for the health care system. Czyżewski et al [19], in a study of the EMST interventions to geriatric patients, showed on a group of patients (n=897) that during interventions pharmaceuticals were used most frequently for respiratory disorders (83%) and neurological disorders (47%, p<0.001). It also showed that patients whose call was due to neurological disorders were statistically more likely to be referred to the ED (76%, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Any preventable transfer Health Problems of Civilization eISSN: 2354-0265, ISSN: 2353-6942 exposes the patient to transport-related complications, and contributes to excessive emergency department occupancy, and increased costs for the health care system. Czyżewski et al [19], in a study of the EMST interventions to geriatric patients, showed on a group of patients (n=897) that during interventions pharmaceuticals were used most frequently for respiratory disorders (83%) and neurological disorders (47%, p<0.001). It also showed that patients whose call was due to neurological disorders were statistically more likely to be referred to the ED (76%, p<0.001).…”
Section: Discussionmentioning
confidence: 99%